2008
DOI: 10.1007/s00125-008-1076-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of myocardial infarction in men and women with type 2 diabetes in the UK: a cohort study using the General Practice Research Database

Abstract: Aims/hypothesis Our primary aim was to establish reliable and generalisable estimates of the risk of myocardial infarction (MI) for men and women with type 2 diabetes in the UK compared with people without diabetes. Our secondary aim was to investigate how the MI risk associated with diabetes differs between men and women.Methods A cohort study using the General Practice Research Database (1992Database ( -1999

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 36 publications
2
36
1
2
Order By: Relevance
“…Similar to the present study, previous studies have shown that diabetes increases the risk of AMI [3][4][5], with a stronger association in women than in men [4,5], and that the most physically active people with diabetes have approximately half the risk of cardiovascular death compared with inactive people with diabetes [24,25]. Moreover, we have recently shown that physical activity modified the association between diabetes and mortality [26].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to the present study, previous studies have shown that diabetes increases the risk of AMI [3][4][5], with a stronger association in women than in men [4,5], and that the most physically active people with diabetes have approximately half the risk of cardiovascular death compared with inactive people with diabetes [24,25]. Moreover, we have recently shown that physical activity modified the association between diabetes and mortality [26].…”
Section: Discussionsupporting
confidence: 89%
“…Diabetes induces vascular dysfunction that predisposes to atherosclerosis [1,2] and is associated with about a twofold increased risk of acute myocardial infarction (AMI) [3][4][5]. Although a broad-based treatment may improve survival in people with diabetes with existing cardiovascular disease, knowledge of effective means for primary prevention of AMI among people with diabetes is still sparse [6].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have generally shown a lesser risk of MI at lower glycemic levels (6,7). However, no population-based real-world studies have evaluated the importance of glycemic control on the development of MI beginning at the diagnosis of diabetes and onward.…”
mentioning
confidence: 99%
“…In general, a two-to fivefold risk of myocardial infarction (MI) exists in T2DM compared with the general population [1]. The relative risk (RR) seems to be higher in women than in men (up to nine and three times, respectively, compared with the general population), although the exact absolute difference in CVD risk between diabetic genders in a given glycemic state is not known [3].…”
Section: Introductionmentioning
confidence: 99%
“…An accumulating body of evidence during the last few decades has established an association between diabetes mellitus [both type 1 (T1DM) and type 2 (T2DM)] and increased risk of cardiovascular disease (CVD) in both genders [1][2][3]. In general, a two-to fivefold risk of myocardial infarction (MI) exists in T2DM compared with the general population [1].…”
Section: Introductionmentioning
confidence: 99%